ANALISIS FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PERTANIAN MENJADI PERUMAHAN DI KABUPATEN SIDENRENG RAPPANG - Zay, Fany Pebriani; R, Fitriani; Haryono, Iranita (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the factors that influence the conversion of agricultural land into housing in Sidenreng Rappang district. The type of research used is quantitative methods. The population used in this research are farmers and developers or housing managers with a sample size of 32 respondents. Data collection was carried out using data primary, namely interview techniques, questionnaires, and observations. Secondary data collection was obtained from various sources such as the Central Statistics Agency (BPS), and journals. The results of the research show that the analysis of factors that influence the conversion of agricultural land into housing in Sidenreng Rappang Regency, namely External Factors, Internal factors and policy factors have a significant influence simultaneously on farmers' decisions to convert their land. Meanwhile, policy factors partially influence farmers' decisions to convert their land, in contrast to external factors, and internal factors do not partially influence farmers' decisions to convert their land in Sidenreng Rappang Regency.